Integrating the Epigenetic and Microbiome-Integrated Mental Health (EMIMH) Framework into Community Health Centers: A Discourse Analysis - Junior, George Akwetey; De-Veer, Theodora Pearl (Yayasan Ilomata, 2024)
This study introduces the Epigenetic and Microbiome-Integrated Mental Health (EMIMH) Framework for Community Health Centers (CHCs), aiming to enhance mental health care delivery. CHCs face challenges including funding constraints, workforce shortages, and difficulties implementing integrated care models for mental health services. The EMIMH Framework proposes integrating epigenetic and microbiome considerations into CHC mental health care, offering a personalized and preventive approach. We conducted a critical discourse analysis of texts from 2018-2024, examining perspectives on integrating advanced biological approaches in CHC mental health care. Results reveal growing interest in epigenetic and microbiome approaches, alongside concerns about implementation barriers, ethical implications, and potential health disparities. The EMIMH Framework presents a promising avenue for improving CHC mental health care, potentially enhancing outcomes and reducing costs. However, successful implementation requires addressing practical, ethical, and equity challenges.